Biosynthetic Pathway for Sex Pheromone Components Produced in a Plusiinae Moth, Plusia festucae - Watanabe, Hayaki; Matsui, Aya; Inomata, Sin-ichi; Yamamoto, Masanobu; Ando, Tetsu (Frontiers in Endocrinology, 2011)
While many Plusiinae species commonly secrete (Z)-7-dodecenyl acetate (Z7-12:OAc) as a key pheromone component, female moths of the rice looper (Plusia festucae) exceptionally utilize (Z)-5-dodecenyl acetate (Z5-12:OAc) to communicate with their partners. GC-MS analysis of methyl esters derived from fatty acids included in the pheromone gland of Plusia festucae showed a series of esters monounsaturated at the ω7-position, i.e., (Z)-5-dodecenoate, (Z)-7-tetradecenoate (Z)-9-hexadecenoate (Z9-16:Me), and (Z)-11-octadecenoate (Z11-18:Me). By topical application of D3-labled palmitic acid (16:Acid) and stearic acid (18:Acid) to the pheromone glands, similar amounts of D3-Z5-12:OAc were detected. The glands treated with D13-labeled monoenoic acids (Z9-16:Acid and Z11-18:Acid), which were custom-made by utilizing an acetylene coupling reaction with D13-1-bromohexane, also produced similar amounts of D13-Z5-12:OAc. These results suggested that Z5-12:OAc was biosynthesized by ω7-desaturase with low substrate specificity, which could introduce a double bond at the 9-position of a 16:Acid derivative and the 11-position of an 18:Acid derivative. Additional experiments with the glands pretreated with an inhibitor of chain elongation supported this speculation. Furthermore, a comparative study with another Plusiinae species (Chrysodeixis eriosoma) secreting Z7-12:OAc indicated that the β-oxidation systems of P. festucae and C. eriosoma were different.